Glass eels (Anguilla anguilla) growth in a recirculating system - ANGELIDIS, P.; POURNARA, I.; PHOTIS, G. (Mediterranean Marine Science, 2005)
On a commercial eel farm, which uses a recirculation system, 400,000 glass eels were farmed for a period of 328 days at 20o – 23o C. The physicochemical parameters of the farm water were kept at normal conditions during the experiment. The NO 2 was kept between 1.0 and 3.0 mg/l. By the end of the experiment, 4,582 kg of fish feed were consumed and 2,939 kg of eels were produced (177,523 eels with mean final individual body weight of 16.6g and mean food conversion ratio of 1.625). The glass eels showed a high variability in their capacity to grow.